Blended Learning Approaches in English Language Teaching Pedagogy - Aryal, Muna (Journal of NELTA, 2024)
This paper presents the impact and eff ectiveness of blended learning strategies in English language teaching (ELT). The study delves into how blended learning, a combination of traditional face-to-face and online learning platforms, enhances student engagement, motivation, and communication. The study utilizes a qualitative research design, employing semi-structured interviews with three experienced English language teachers. The findings reveal that blended learning provides flexible and individual learning opportunities to learners which significantly enhances their engagement and learning outcomes. However, teacher’s flexibility and continued professional development are essential for the successful implementation of blended learning. The study highlights the need for institutional support to address the challenges of integrating blended learning into ELT, ultimately contributing to a more dynamic and effective teaching methodology.